Power converters for a small islanded microgrid based on a micro wind turbine and an battery energy storage system - Duarte, Rafael Eduardo Gomes (2018)
The growing awareness of the environmental issues has begun to change the traditional scheme of electric energy production along the last years, where fossil fuels based systems are a major cause for this change. For this reason, renewable energy sources are emerging as an ecologically way to produce energy. However, associated with the renewables integration into power grids, new challenges and opportunities arises. Although the crescent energy production, there are still 1.2 thousand million people without access to electricity, since some places are difficult to reach or is expensive to extend the power grid. As a contribution to solve this problem, this paper proposes a solution based on a Permanent Magnet Synchronous Generator (PMSG) micro wind turbine and a Battery Energy Storage System (BESS) to create an islanded microgrid. The developed and required power electronics hardware is presented and described in the paper, as well as the digital control platform, where is implemented the control system, with algorithms such as the Maximum Power Point Tracking (MPPT), used to extract the maximum power available at each instant in the micro wind turbine. A detailed analysis based on simulation results is presented and, aiming to verify the feasibility of the proposed solution, a laboratorial prototype was developed and experimental results in transient and steady state operation are presented and discussed in the paper.